Lesson in Transition Interactive of the Methods Use Efficiency - Ishankhodjayeva Feruza Abduboriyevna (International Journal on Integrated Education, 2023)
Present in the day lesson in transition interactive of the methods use students to lessons interest more is increasing. That's why is also interactive for methods by learning him to practice application reach each one from the teacher is a requirement remains.